Чутливість парієтальних клітин до стимуляторів шлункової секреції після тривалого введення омепразолу - Цирюк, Oлена; Берегова, Тетяна; Tsyryuk, Оlena; Beregova, Tatyana (Східноєвропейський Національний університет імені Лесі Українки, 2015)
У роботі показано, що 28-денне пригнічення секреції гідрохлоридної кислоти блокатором H+ -K+ -АТФази омепразолом призводить до падіння чутливості парієтальних клітин до пентагастрину та гістаміну, але не впливає на секреторну відповідь, стимульовану карбахоліном.. The aim of our study was to investigate the effect of stimulants of gastric acid secretion on secretory function of the stomach after a long-term hypoacidity induced by the introduction of the H+ -K+ -ATPase blocker omeprazole. The experiments were carried out on white nonlinear male rats. On a day after last 28-day administration of omeprazole we investigated the basal and stimulated (by histamine, pentagastrin, carbachol) gastric acid secretion using method of isolated stomach perfusion by Ghosh and Shild. So it was shows that hypergastrynaemia caused by 28-days inhibition of hydrochloric acid secretion of blocker H + -K + -ATPase omeprazole leads to falling the sensitivity of parietal cells to pentagastrin and histamine, but does not affect on the secretory response evoked by carbachol.
The Sensitivity of the Parietal Cells to Gastric Secretion Stimulators After a Long-term Injection of Omeprazole.
Keywords: шлункова секреція; омепразол; гістамін; пентагастрин; карбахолін; гіпергастринемія; gastric acid secretion; omeprazole; histamine; pentagastrin; carbahol; hypergastrineamia